Cannabis, alcohol and cigarette use during the acute post-concussion period. (2nd January 2020) - Lawrence, David W.; Foster, Evan; Comper, Paul; Langer, Laura; Hutchison, Michael G.; Chandra, Tharshni; Bayley, Mark
ABSTRACT: Objective : To document the prevalence of acute post-concussion cannabis, alcohol and cigarette use and their association with clinical recovery and symptom burden. Methods : A prospective cohort study was conducted. Concussions were physician-diagnosed and presented to the emergency department and concussion clinic within 7 days post-injury. Participants were assessed weekly and followed for a minimum 4 weeks. A survival analysis (using physician-determined recovery to both cognitive and physical activities) in addition to a weekly symptom score analysis was conducted. Results : A total of 307 acute concussions with a mean age of 33.7 years (SD, 13.0) were included. Acute post-concussion cannabis, alcohol and cigarette use were identified in 43 (14.0%), 125 (40.7%) and 61 (19.9%) individuals. Acute cannabis, alcohol and cigarette use were not associated with recovery to cognitive ( p > .05) or physical activity ( p > .05). Acute cigarette use was associated with a higher unadjusted symptom severity score at week1 ( p = .003). Acute cannabis use was associated with lower symptom severity scores at week-3 ( p = .061) and week-4 ( p = .029). Conclusion : In conclusion, cannabis, alcohol and cigarette use were prevalent in the acute period post-concussion; however, were not observed to impact recovery within the first 4 weeks post-injury. Amongst unrecovered individuals, acute cannabis use was associated with lower symptom burden, while cigarette use was associated with greater initial symptom burden.